The value of market research information : how do clients of market research services construct value from their usage of market research information? - Said, Emanuel (Cranfield University, 2011)
A significant global industry, the provision of market research is a business to business service where market research organizations provide market research information to customers, who in turn, need to make informed decisions about marketing strategy alternatives. This study involves a systematic literature review of the influences impacting on the use of market research information. It expounds the conditions, factors and mechanisms that induce or hinder the process of use among client organization users. In so doing, this investigation provides a descriptive assessment of the body of knowledge from which this study draws. This study proposes a theoretical framework of the reported conditions, factors and mechanisms that enhance or hinder the process at different stages of usage of market research. Influences like (user) organization’s strategy, structure, market philosophy, stance in the market and access to market research suppliers have a direct effect on how user organizations seek and apply market research information. The process of usage features seven phases, contrasting against the four or five phases that are typically reported in literature. Application of market research information in marketing decisions may follow one of three possible types of application: instrumental, conceptual and symbolic. This study also explores the various limitations in our understanding of this phenomenon. Relying on a number of published positivist contributions, our understanding of this process is composed of narrow views of specific causalities, each investigated independently from the rest. These result in an incomplete, inconsistent picture about a phenomenon. For instance, influences impacting on transformation and dissemination steps remain largely unknown, as are the factors impacting on application of market research information like symbolic use. Equally, published positivist researchoften relies on a single informant approach that is assumed to represent the reality of an entire organization. The study concludes with considerations about future work that may form part of my PhD research, intended to address a selection of gaps in the existing body of knowledge about this phenomenon.
Keywords: Market research use; instrumental use; conceptual use; symbolic use; market research firms; market based learning; organizational learning; knowledge management